Chile Fiscal Policy Management; Polityka nadwyzk̇i budzėtowej w Chile - Ryszard Piasecki; Erico Wulf Betancourt (Comparative Economic Research. Central and Eastern Europe, 2013)
A budget surplus arises in a country when the total revenue earnings surpass expenditures in a particular financial year. Having a budget surplus is very important in the sense that it brings about a decrease in the net public debt, while the public debt is increased in the event of a budget deficit. Both budget deficits and budget surpluses also exert indirect influences on taxpayers. Normally, it is not essential on the part of the government to maintain a budget surplus, though it needs to be very careful when running a budget deficit to have the proper buffer. – – Od kilkunastu lat polityka fiskalna Chile jest oparta na koncepcji roẃnowagi budzėtowej. W przeciwienśtwie do roẃnowagi efektywnej, ktoŕa pokazuje aktualna sytuacje fiskalna, ta pierwsza odzwierciedla sŕednioterminowa perspektywe budzėtu. Nadrzedna zasada systemu jest szacowanie wpływu netto z podatkoẃ w okresĺonym sŕednim okresie. Wydatki musza bycṕrzy tym roẃne wpływom. W praktyce oznacza to oszczedzanie podczas wzrostu gospodarczego oraz wydawanie uzyskanej nadwyzk̇i w okresie, kiedy wpływy z podatkoẃ sa mniejsze.
Keywords: 330